2013
DOI: 10.1093/nar/gkt1077
|View full text |Cite
|
Sign up to set email alerts
|

Distinct substrate specificities of Arabidopsis DCL3 and DCL4

Abstract: In Arabidopsis thaliana, Dicer-like 3 (DCL3) and Dicer-like 4 (DCL4) cleave long, perfect double-stranded RNAs (dsRNAs) into 24 and 21 nucleotides (nt) small interfering RNAs, respectively, which in turn function in RNA-directed DNA methylation and RNA interference, respectively. To reveal how DCL3 and DCL4 individually recognize long perfect dsRNAs as substrates, we biochemically characterized DCL3 and DCL4 and compared their enzymatic properties. DCL3 preferentially cleaves short dsRNAs with 5′ phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 40 publications
18
84
0
Order By: Relevance
“…These results support the idea that exogenously supplied HYL1 antagonizes BYL-maintained dsRNA processing activities relying on endogenous DCL3 and DCL4, while exogenous DRB4 assists the DCL4-mediated activity specifically. Similar dsRNA-processing properties have been established previously in Arabidopsis cell extracts (Nagano et al 2014).…”
Section: Resultssupporting
confidence: 82%
“…These results support the idea that exogenously supplied HYL1 antagonizes BYL-maintained dsRNA processing activities relying on endogenous DCL3 and DCL4, while exogenous DRB4 assists the DCL4-mediated activity specifically. Similar dsRNA-processing properties have been established previously in Arabidopsis cell extracts (Nagano et al 2014).…”
Section: Resultssupporting
confidence: 82%
“…S1a). The short length of P4RNAs fits well with the specific preference of DCL3 for short (30 to 50 base pairs, bp) dsRNA substrates (Nagano et al, 2014), consistent with the hypothesis that these short P4RNAs serve as the precursors for siRNA biogenesis.…”
Section: Resultssupporting
confidence: 81%
“…Interestingly, biochemical characterization of Arabidopsis DCL3 and DCL4 revealed that DCL3 preferentially cleaves short dsRNAs (37 to 50 nucleotides), whereas DCL4 preferentially cleaves long dsRNAs (Nagano et al, 2014). This result is consistent with DCL4 producing phased 21-nucleotide siRNAs over a long distance on TAS genes (Vazquez et al, 2004;Allen et al, 2005), whereas DCL3 does not.…”
Section: Discussionmentioning
confidence: 56%